Programas de preparação para aposentadoria: instrumentos efetivos de responsabilidade social nas universidades públicas federais de ensino superior - Fonseca, Adilce das Graças (2019)
This research had as a starting point to investigate what actions the Federal Public Universities of Higher Education are promoting to assist the servants in the process of preparation for retirement. It is considered that practices with this purpose can be effective instruments for a socially responsible management, since this theme is approached in the 'social dimension" of Social Responsibility. In order to reach the proposed objective, we used the exploratory descriptive research, as instruments for data collection. The documentary analysis of 61 Institutional Development Plans was made available on the electronic portal of the universities, in addition to the application of a questionnaire. The main results indicate that only 20 institutions include in their planning actions and proposals of practices of internal social responsibility that aim at the preparation for retirement. With the application of the questionnaire obtained answers from 38 universities, the data obtained allowed to outline the format and implementation of the programs used by 24 universities in order to promote the preparation for the retirement of the employees of these institutions. These data made it possible to identify a picture of the theme in universities, which, by promoting an alignment of their planning with the execution of these practices, as well as strengthening working relationships also reflect responsible social commitment. As a suggestion for future research, it is considered important to relate the preparation for retirement with tools for knowledge management in public institutions, aiming to retain and disseminate knowledge, besides preserving institutional history.